2016
DOI: 10.1007/s10393-016-1186-9
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus laevis and Emerging Amphibian Pathogens in Chile

Abstract: Amphibians face an extinction crisis with no precedence. Two emerging infectious diseases, ranaviral disease caused by viruses within the genus Ranavirus and chytridiomycosis due to Batrachochytrium dendrobatidis (Bd), have been linked with amphibian mass mortalities and population declines in many regions of the globe. The African clawed frog (Xenopus laevis) has been indicated as a vector for the spread of these pathogens. Since the 1970s, this species has been invasive in central Chile. We collected X. laev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 59 publications
(73 reference statements)
2
35
0
Order By: Relevance
“…Xenopus laevis is considered as an effective vector capable of disseminating Bd into new regions (Soto‐Azat et al., ) and thus represents a possible route of introduction of Bd GPL into Chile. The earliest evidence of Bd in Chile is from a four‐eyed frog ( Pleurodema thaul ) individual collected from Concepción in 1970 (Soto‐Azat et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xenopus laevis is considered as an effective vector capable of disseminating Bd into new regions (Soto‐Azat et al., ) and thus represents a possible route of introduction of Bd GPL into Chile. The earliest evidence of Bd in Chile is from a four‐eyed frog ( Pleurodema thaul ) individual collected from Concepción in 1970 (Soto‐Azat et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, there is a knowledge gap on the molecular diversity of Bd genotypes occurring in most areas within this region. For instance in Chile, Bd is widespread, infecting native and invasive anurans, but no attempt has been conducted so far to isolate the fungus or to conduct comparative molecular analyses (Soto‐Azat et al., , ; Valenzuela‐Sánchez et al, ). This limits our capacity to adequately understand the emergence and epidemiology of chytridiomycosis in the region.…”
Section: Introductionmentioning
confidence: 99%
“…First, it might be indicative of human‐mediated transmission of the fungus (e.g., intentional or accidental introduction of Bd with infected animals or via the transportation of contaminated water or damp substrates; e.g., Fisher and Garner , Soto‐Azat et al. ). This is consistent with other studies that have also found a positive relationship between Bd occurrence and human influence at both local (Adams et al.…”
Section: Discussionmentioning
confidence: 99%
“…Berger et al, 1998;Bosch, Martinez-Solano and Garcia-Paris, 2001;Olson et al, 2013). Xenopus laevis is also known as an asymptomatic carrier of ranaviruses (Robert et al, 2014) and a high prevalence of these viruses has been detected in at least one location where it is invasive (Soto-Azat et al, 2016).…”
Section: Discussionmentioning
confidence: 99%